Stakeholder Collaboration in Flood Disaster Management in Labansari Village - Ganuardi Pradipta; Arfindi Yunanda Santoso; Saipullah; Fahri Syarief (Prospect Publishing, 2023)
This study aims to describe stakeholder collaboration in flood disaster management in Labansari Village. The research method is a qualitative method, with data collection techniques, interview, observation, and documentation. Labansari Village is a village located in East Cikarang District, Bekasi Regency. Geographically, Labansari Village is a meeting point for 2 rivers, the Citarum River and Cibeet River. So that at the meeting point of the two rivers there is an increase in water level which makes the river overflow. This resulted in Labansari Village being flood, even though there was no rain in the village. This event often occurs every year. Therefore, people are used to floods. However, the frequent occurrence of floods does not increase public awareness. On this basis, there is a need for collaboration stakeholder, from the community, the government, to companies in efforts to deal with flood disaster. Labansari village community has become aware of flood disaster management through this collaboration. Then formed Tim Kerja Masyarakat Siaga Bencana (TKMSB). TKSMB has 6 functions, Tim Reaksi Cepat (TRC) & Informasi, Shelter, Logistik/Dapur Umum, Evakuasi, Medis, Keamanan. The existence of this collaboration has produced real results with the existence of an early warning system, vlllage regulations, and the role of TKMSB. Flood disasters that occur repeatedly can be minimized by collaboration stakeholders.